PENGARUH PEMBERIAN DOSIS BOKASIH KULIT BUAH KAKAO TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI (Capsicum annuum L. ) - Julianus Jeksen (AGRICA, 2013)
This research aims to know the effect of dosing cacao rind bokashi fertilizer to the growth and the increase of chilli plants yield and also to know the optimum dose of bokashi which can provide the optimum growth and yield. The design used in this experiment is Randomized Block Design (RBD). The treatment used are P0 (without cacao rind fertilizer), P1 (cacao rind fertilizer 10 tons ha-1 = 5.6 kg/ptk), P2 (cacao rind fertilizer 20 tons ha-1 = 11.2 kg/ptk), P3 (cacao rind fertilizer 30 tons ha-1 = 16.8 kg/ptk), P4 (cacao rind fertilizer 40 tons ha?1= 22.4 kg/ptk). The variable of the observation in this research is the height of the plants, the number of leaves, the leaf width, the fruit weight tan?1, the fruit weight ha?1. The result of this research indicates that the dosing of cacao rind bokashi fertilizer can influence the plant's height with the total average of 24.52%, the average number of leaves with a total of 14.56%, and the average leaf width with a total of 29.55 %, and the total of fruits tan?1 31,46%, the fruit weight tan?1 29.17%, the fruit weight ha?1 28.67%. The optimum dose of cocoa rind bokashi 40 tons ha?1 can promote the optimum growth and yield of chilli plants.